Factors affecting IUD discontinuation in women referring to Shahrekord health centers in 2010 - Marzie Hosseini; Faranak Safdari; Sara Hosseini; Javad Malek Anzabi; Tahmine Salehian (Majallah-i Bālīnī-i Parastārī va Māmāyī, 2012)
Background and aims: The continued use of a contraceptive method is a reliable indicator. Intrauterine contraceptive device is very safe, highly effective reversible and inexpensive family planning method which its essential feature is their long duration of action. The aim of this study was determination of affecting factors in early IUD expulsion in women who referred to health centers in Shahrekord. Methods: This cross-sectional study was performed on 182 women who referred to health centers in Shahrekord for early discontinuation of the intrauterine device (IUD). Convenience sampling was done based on the target. The data were gathered via interview and questionnaire. The data were transferred to SPSS16 software and analyzed statistically using T-test, Chi–square, One-way ANOVA, and Pearson correlation. P-value less than 0.05 was considered significant. Results: In this study, the most important cause of early IUD expulsion was bleeding (29.2%), desire for pregnancy (26.7%), displacement of IUD (14.9%), infection (11.8%), abdominal pain (7.5%) and menstruation disorder (5.6%) respectively. There was a significant relationship between counseling before IUD insertion with side effects and use duration of this device (P=0.001 and P=0.009). The cause of choosing IUD as a contraceptive method in 83.4 Percent from Not counseled samples was No need to remind and in 76/5 Percent of counseled was for long duration of action. Conclusion: In this study, the most common cause for IUD removal was its side effects, but tendency to pregnancy, was the second leading cause of premature removal for IUD as well. So, It is suggested with Consulting and proper selection of candidates and education about the effects Accessories and regular examinations and treatment as soon as possible for evaluation and treatment of complications of IUD continuation rates added.